The Influence of Discipline on Teacher Motivation in Public Elementary Schools in Makassar - Nur Aeni; Mattalatta Mattalatta; Tajuddin Malik; Ansar Ansar; Kurniawaty Sandra; Nur Naninsih (International Journal of Economics, Commerce, and Management, 2024)
This study aims to investigate the influence of discipline on teacher motivation in public elementary schools in Makassar. The research employs descriptive and confirmatory approaches. The descriptive approach seeks to explain the data presented in tables, figures, and graphs, while the confirmatory approach is used to confirm the influence of exogenous variables (discipline, competence, and leadership) on the intervening variable (motivation) and the endogenous variable (performance). The research was conducted in 58 public elementary schools across three districts: Tallo, Ujung Tanah, and Wajo, with the study period estimated to last three months, from April to July 2024. The data types include primary data obtained through observations, questionnaires, and interviews with respondents, as well as secondary data from documents, reports, books, the internet, and related journals. From 300 respondents, the results indicate that the overall perception of motivation is positive, with an average score of 3.68. The indicators of attendance and active involvement received the highest score (3.75), followed by enthusiasm in teaching (3.77), while the indicators of energy in teaching (3.59) and the drive for student progress (3.64) received lower scores. These findings suggest that, although the majority of respondents agree that motivation is an important factor in performance, 18.48% of respondents do not fully agree. The study also found a positive and significant relationship between teacher discipline and their performance, mediated by motivation. Discipline helps teachers manage tasks and time effectively, which in turn enhances both motivation and performance. In conclusion, to improve teaching quality, it is essential for schools to support teacher motivation and discipline through professional development programs and to create a conducive environment.